Religious and social dynamics of the Niasse branch of the Tijâniyya among youth in Dakar (Senegal) and Lomé (Togo) - (:unkn) unknown (My University, 2013)
Panel Citizen participation, religion and development: new social actors for a changing world?, mod. Marie Nathalie LeBlanc http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2030
Keywords: African Research